2017
DOI: 10.1039/c7cp02524f
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structures of Au–Rh bimetallic nanoclusters supported on a thin film of Al2O3/NiAl(100)

Abstract: Self-organized alloying of Au with Rh in nanoclusters on an ordered thin film of AlO/NiAl(100) was investigated via various surface probe techniques under ultrahigh-vacuum conditions and calculations based on density-functional theory. The bimetallic clusters were formed on the sequential deposition of vapors of Au and Rh onto AlO/NiAl(100) at 300 K. The formation was more effective on the oxide seeded with Rh, since all post-deposited Au joined the pregrown Rh clusters; for metal deposition in the reverse ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 61 publications
5
17
0
Order By: Relevance
“…This preparation route cannot be performed on pure Al as only amorphous Al 2 O 3 can be grown as thin layer, whereas the formation of crystalline Al 2 O 3 on Al requires thicker layers or proceeds in island growth at high temperature. 18 The synthesis of well ordered oxide lms on metallic substrates is used to produce model support surfaces for heterogeneous catalysts that may host metal clusters, 19,20 metal particles [21][22][23][24][25][26][27] and also metal oxide particles. [28][29][30] The oxidation of Ni 3 Al(111) 7,8,[31][32][33][34] and especially the formation of the so called (O67 Â O67)R12.2 surface oxide is of great interest, 33,35 because it has nano-template properties that can be used to stabilize almost monodisperse distributions of metal particles on the thin alumina support.…”
mentioning
confidence: 99%
“…This preparation route cannot be performed on pure Al as only amorphous Al 2 O 3 can be grown as thin layer, whereas the formation of crystalline Al 2 O 3 on Al requires thicker layers or proceeds in island growth at high temperature. 18 The synthesis of well ordered oxide lms on metallic substrates is used to produce model support surfaces for heterogeneous catalysts that may host metal clusters, 19,20 metal particles [21][22][23][24][25][26][27] and also metal oxide particles. [28][29][30] The oxidation of Ni 3 Al(111) 7,8,[31][32][33][34] and especially the formation of the so called (O67 Â O67)R12.2 surface oxide is of great interest, 33,35 because it has nano-template properties that can be used to stabilize almost monodisperse distributions of metal particles on the thin alumina support.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29] In a number of studies Au and Rh were sequentially evaporated by physical vapor deposition (PVD) on oxide single crystalline surfaces. 18,19,21,22,28,29 When first Au nanoparticles were prepared on a rutile TiO 2 (110) surface followed by evaporation of Rh, an efficient place exchange already occurred at room temperature, leading to the incorporation a great part of Rh atoms into the subsurface of Au clusters, while the outermost layer still mostly consisted of gold. 18 The driving force for this process is the smaller surface energy of Au compared to that of Rh (1.283 J/m 2 for Au(111) and 2.472 J/m 2 for Rh(111)).…”
Section: Introductionmentioning
confidence: 99%
“…While computational analysis of the interaction of Au with Rh(111) is the subject of the present paper as a continuation of our recent experimental studies, 21,31 other relevant surfaces were addressed in previous works. 24,28,[32][33][34] Scanning tunneling microscopy (STM) and Auger electron spectroscopy (AES) investigations showed that Rh forms three dimensional (3D) islands on Au(111) at room temperature according to Volmer -Weber growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations